Systematic review: e-cigarettes vs. conventional cigarettes - Mateusz Janik; Barbara Ufnalska; Joanna Rychlewska-Duda; Justyna Lisiecka; Artur Fabijański; Anna Konarska; Anna Machowiak; Michał Nowak; Wojciech Firlej; Adrianna Dukacz (Journal of Education, Health and Sport, 2025)
Introduction